Mapeamento elementar por microfluorescência de raios X em esferoides de linhagens prostáticas tumorais suplementados com zinco - Rocha, Karolynne de Araujo Marins José (2019)
Prostate cancer is a highly prevalent disease and, except for non-melanoma skin cancer, it ranks second among malignancies affecting men around the world. Trace elements are involved in many normal and pathological cellular processes. X-ray microfluorescence (microXRF) is an advanced high-spatial resolution tool, sensitivity for multielementar and non-destructive trace element analysis. The objective of this study was to investigate the elemental distribution in spheroids obtained from prostatic cell lines using X-ray microfluorescence (SR-microXRF): normal immortalized cell line (RWPE1), androgen dependent tumor cell line (LNCaP) and androgen-independent tumor cell line (DU145), following supplementation with ZnCl2. Studies suggest that increasing zinc in the prostate may be a potential therapeutic strategy. The measurements were performed with a standard 45 º incidence geometry, excited by a white beam using a 25 µm pixel and a 300 ms / pixel acquisition time in the XRF light line at the National Synchrotron Light Laboratory (Campinas, Brazil). The results of SR-microXRF analysis showed different iron, copper and zinc behaviors in normal and prostate tumor cell lines. Thus, our model may represent an important tool to understand the development and progression of this disease.